2006
DOI: 10.1557/jmr.2006.0385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reaction parameters on the electrochemical formation of multilayer films composed of manganese oxides and tetra-alkylammonium ions

Abstract: Multilayered manganese oxide films were prepared on a platinum electrode by potentiostatic oxidation of aqueous Mn2+ ions in the presence of n-tetra-alkylammonium compounds. Alkylammonium cations were intercalated between manganese oxide layers to balance the negative layer charge. Effects of several preparative parameters such as the size of alkylammonium molecules, counteranions, and bath composition on the structure of products were investigated. The interlayer distance of the products increased with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The previous study [15] indicated that the amount of alkali cations depends on the bath composition and the applied potential. From the X-ray photoelectron spectroscopy, x was estimated to be approximately 0.35 in this study.…”
Section: Electrochemical Synthesis and Characterizations Of Manganesementioning
confidence: 98%
See 1 more Smart Citation
“…The previous study [15] indicated that the amount of alkali cations depends on the bath composition and the applied potential. From the X-ray photoelectron spectroscopy, x was estimated to be approximately 0.35 in this study.…”
Section: Electrochemical Synthesis and Characterizations Of Manganesementioning
confidence: 98%
“…Recently, a new electrochemical method was developed at Yamaguchi University to synthesize birnessite-type layered MnO 2 intercalated with organic molecules such as alkylammonium ions [14,15] and polycations [16]. The electrodeposition process involves a potentiostatic oxidation of aqueous Mn 2+ ions in the presence of a small amount of organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Hereafter, this product is abbreviated as Bu-Br in order to distinguish from the Bu 4 NBr reagent. 1, 2, 3, and 4), indicative of a layered structure, as expected for the formation of birnessite-type layered Mn oxide (4)(5)(6)(7)13). With an increase in time of electrolysis, the diffraction peaks increase in intensity without broadening, clearly indicating the growth ECS Transactions, 16 (46) 37-43 (2009) of Mn oxide crystals.…”
Section: Resultsmentioning
confidence: 65%
“…The separation of the peak energy ( E) is sensitive to the oxidation state of manganese. According to the linear relationship between the average oxidation state of manganese and the E value in the literature [25], the E value (4.86 eV) obtained corresponds to an average oxidation level of 3.7-3.8, which is typical of birnessite-type manganese oxide [26]. In the O 1s region (Fig.…”
Section: Resultsmentioning
confidence: 82%